Evaluating Sustainability Research in Argentine Higher Education - Arias Valle, Maria Belen (2025)
This study analyzes the integration of sustainability into the research activities of Argentine higher education institutions (HEIs), both public and private. Through a quantitative approach, 132 HEIs were evaluated regarding the presence of sustainability research lines, the inclusion of this topic in strategic plans, and the existence of specialized institutes and academic publications. The results indicate that only 26% of HEIs have established research lines on sustainability, with greater participation from public universities. However, the overall commitment is uneven, with only 55% of institutions including sustainability in their strategic plans. The limited presence of observatories, specialized journals, and research centers in sustainability constrains the ability of Argentine HEIs to influence national and international agendas in this field. This study highlights the need for stronger policies and incentives to promote sustainability research. The study concludes by emphasizing that while progress has been made, it is imperative to adopt a systematic and strategic approach for Argentine HEIs to effectively contribute to sustainable development.